ANA MIRANDA E A FIGURAÇÃO DE ESCRITORES BRASILEIROS EM A ÚLTIMA QUIMERA - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
This is a work dedicated to analyze the novel A última quimera (The last chimera) by Ana Miranda, with main objective to investigate how two characters writers figuration in the narrative, the poets Augusto dos Anjos and Olavo Bilac. From then on, understand how the reconstruction of a moment in the history of literature, by which showed the expression of critical thinking about the poems of these two writers and about own literary history that was formed at the time. In this way, we are dedicated to check others literary works of the same author who also present writers as characters. We seek to see what the academic criticism argues about the novel in question and know the reason for the growing interest in fictionalization of writers recognized by the literary canon. To this end, we consulted two scholars who have dedicated to investigate some literary productions as these: the researcher Leyla Perrone-Moisés and the critic Carlos Reis.
Keywords: Ana Miranda; Figuração de escritores; Crítica acadêmica; História da literatura; Ana Miranda; Figuration of writers; Academic criticism History of literature; CNPQ::LINGUISTICA, LETRAS E ARTES